Bone graft augmentation of comminuted radial neck fractures improves the initial stability of plate fixation: a biomechanical study - Hockmann, Jan Philipp; Heck, Vincent; Theißen, Niklas; Prescher, Andreas; Leschinger, Tim; Müller, Lars Peter; Hackl, Michael (Journal of shoulder and elbow surgery, 2025)
Background - Using modern implants, even complex radial head and neck fractures can often be reconstructed. However, metaphyseal comminution is associated with delayed bone healing and an increased risk for loss of reduction. Hence, this biomechanical in-vitro study intended to evaluate the mechanical stability of a bone graft from the ipsilateral proximal ulna in plate fixation of comminuted radial neck fractures. - Methods - Osteotomies at the level of the radial neck with a 3 mm defect were created on 20 fresh-frozen proximal radius specimens to simulate metaphyseal comminution. Fixation was performed with a locking radial head plate in group A and with an additional structural bone graft from the ipsilateral ulna in group B. Cyclic loading from 5-100 N was performed and axial displacement and stiffness were evaluated. - Results - The axial displacement was larger in group A (0.81 ± 0.24 mm) than in group B (0.52 ± 0.27 mm) (P = .02). Group B had a higher axial stiffness compared to group A (300 (127-958) N/mm vs. 163 (82-209) N/mm, P = .015). - Conclusion - In the case of metaphyseal comminution of radial head/neck fractures, additional bone graft augmentation from the proximal ulna results in significantly increased stability of locking plate fixation. Future clinical research should focus on whether this leads to improved union rates of these challenging fractures.